2003
DOI: 10.1021/ac034064e
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Voltage Capillary Electrochromatography

Abstract: A phenomenon was found whereby the application of an alternating voltage to a capillary column can vary the capacity factor of a sample solute. The alternating voltage-induced variation in the capacity factor was studied using an anion exchange mini-bed (a short capillary column 12 mm long). The capacity factor varied according to both the amplitude and frequency of an applied alternating voltage. The variation greatly depended on the kinds of sample solutes and packing materials. A new separation mode for cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Tsuda et al have also shown that the retention factors of neutral [167,168] and charged [169,170] analytes can be affected and controlled by application of an electric field. Lately these authors have also shown similar results with the use of alternating voltage [171].…”
Section: Controlling the Retention With Electricitysupporting
confidence: 60%
“…Tsuda et al have also shown that the retention factors of neutral [167,168] and charged [169,170] analytes can be affected and controlled by application of an electric field. Lately these authors have also shown similar results with the use of alternating voltage [171].…”
Section: Controlling the Retention With Electricitysupporting
confidence: 60%
“…Tsuda et al have also shown that retention factors can be affected and controlled by application of an electric field on neutral [36,37] and charged [38,39] analytes. Lately, they have also shown similar results with the use of alternating voltage [40].…”
Section: Introductionsupporting
confidence: 52%
“…The CEC method possesses high separation efficiency due to the very flat flow profile, which is generated by the electroosmotically driven mobile phase. Depending on both assisted pressure and electric field, the pCEC separation efficiency is between that of CEC and HPLC [40][41][42]. When the electroosmotic flow is predominantly responsible for driving the flow of mobile phase, high separation efficiency could be obtained.…”
Section: Effect Of Assisted Pressure and Separation Voltage On Separamentioning
confidence: 99%